Cognitive impairment in Chinese traumatic brain injury patients: from challenge to future perspectives - Liu, Tao; Yu, Shaohui; Liu, Mingqi; Zhao, Zhihao; Yuan, Jiangyuan; Sha, Zhuang; Liu, Xuanhui; Qian, Yu; Nie, Meng; Jiang, Rongcai (Frontiers in Neuroscience, 2024)
Traumatic Brain Injury (TBI) is a prevalent form of neurological damage that may induce varying degrees of cognitive dysfunction in patients, consequently impacting their quality of life and social functioning. This article provides a mini review of the epidemiology in Chinese TBI patients and etiology of cognitive impairment. It analyzes the risk factors of cognitive impairment, discusses current management strategies for cognitive dysfunction in Chinese TBI patients, and summarizes the strengths and limitations of primary testing tools for TBI-related cognitive functions. Furthermore, the article offers a prospective analysis of future challenges and opportunities. Its objective is to contribute as a reference for the prevention and management of cognitive dysfunction in Chinese TBI patients.